2020
DOI: 10.3389/fpsyg.2020.572455
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Sided Effect of Leader Unethical Pro-organizational Behaviors on Subordinates’ Behaviors: A Mediated Moderation Model

Abstract: Research suggests that unethical pro-organizational behavior (UPB) has two conflicting characteristics: unethical and pro-organizational. However, little attention has been paid to the negative and positive outcomes of UPB. Therefore, the present study aimed to fill this gap by examining a mediated moderation model on the effects of leader UPB on their subordinates' behaviors. Based on social information processing theory and three-wave survey data from 204 supervisor-subordinate dyads in China, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…According to a past study by Chhabra and Srivastava (2022), organizational sustenance, as well as leadership, are affirmative organizational aspects which fuel the manifestation of unethical conduct in organizational boundaries. These asserting aspects enhance identification as well as the commitment of workers to their organizations; consequently, workers detriment societal comforts to deliver benefits to their organization by executing unethical pro-organizational behaviors (Umphress et al, 2010;Wen et al, 2020). The outcomes of this study also established the negative association between spiritual leadership and UPB by supporting hypothesis 1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to a past study by Chhabra and Srivastava (2022), organizational sustenance, as well as leadership, are affirmative organizational aspects which fuel the manifestation of unethical conduct in organizational boundaries. These asserting aspects enhance identification as well as the commitment of workers to their organizations; consequently, workers detriment societal comforts to deliver benefits to their organization by executing unethical pro-organizational behaviors (Umphress et al, 2010;Wen et al, 2020). The outcomes of this study also established the negative association between spiritual leadership and UPB by supporting hypothesis 1.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, Inam et al (2021) disclosed that LMX partially mediates the association amid leadership and employee behavior or conducts in work settings. Wen, Chen, Chen, and Cao (2020) as well demonstrated that employees infer the actions of their seniors at work and reflect their behavior following their interpretations, which in turn roots diverse behavior in variant individuals. Moreover, Luu (2023); Uymaz and Arslan (2022) revealed that different leadership approaches, such as servant and responsible leadership fortified employees to show UPB.…”
Section: Spiritual Leadership and Upbmentioning
confidence: 99%
“…First, up to researcher's knowledge several previous studies focused mainly on the relationship between leaders' Machiavellianism and employees' (OCB) (Hartog & Belschak, 2012;Frazier & Jacezko, 2020;Wen et al, 2020;De Hoogh et al, 2021;Srivastava et al, 2022). Therefore, this study proposes a model in which employees' Machiavellianism influence employees'(OCB) instead of leaders' Machiavellianism.…”
Section: Research Gapmentioning
confidence: 99%
“…Subordinate UPB, however, implicates contradictory information to supervisors, including both positive (i.e., pro-organizational) and negative (i.e., unethical) cues, which results in paradoxical perceptions of and reactions to it ( Wen et al, 2020 ). On the one hand, people tend to lose trust in those who engage in unethical behaviors, believing that they are unreliable because of their questionable standards and principles ( Norman et al, 2010 ; Ng and Feldman, 2015 ; Fehr et al, 2020 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%